2008
DOI: 10.1021/ic8005663
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Sensitization of Lanthanide Luminescence by Tetrazole-Based Polydentate Ligands

Abstract: Tetrazolate groups have been included by a convenient synthetic route in diverse ligand topologies, which have allowed the incorporation of lanthanide ions into highly luminescent double- and triple-helical complexes, demonstrating their potential for the expansion of lanthanide chemistry and the development of lanthanide-based applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…It should also be noted that some of the aromatic rings in the ligands are slightly bowed, a feature that is often found in complexes with high coordination numbers even in phenanthroline 40 rings. 32 A bowed arrangement of 5 is also observed in the crystal structure of Y (5) 33 In this crystallographic 50 structure, the metal ion occupies the center of an irregular bicapped trigonal prismatic assembly of nitrogen atoms that is close to a square antiprismatic arrangement. The induced paramagnetic shifts δ i were computed from the spectra of Yb (5) as a reference.…”
Section: Nuclear Magnetic Resonance and Theoretical Studiesmentioning
confidence: 79%
“…It should also be noted that some of the aromatic rings in the ligands are slightly bowed, a feature that is often found in complexes with high coordination numbers even in phenanthroline 40 rings. 32 A bowed arrangement of 5 is also observed in the crystal structure of Y (5) 33 In this crystallographic 50 structure, the metal ion occupies the center of an irregular bicapped trigonal prismatic assembly of nitrogen atoms that is close to a square antiprismatic arrangement. The induced paramagnetic shifts δ i were computed from the spectra of Yb (5) as a reference.…”
Section: Nuclear Magnetic Resonance and Theoretical Studiesmentioning
confidence: 79%
“…Conversely, a preliminary study from our group indicated that tetrazolates can act as efficient sensitizers of lanthanide luminescence. [16] Moreover, tetrazolates have attracted considerable interest in coordination chemistry due to their [17] p-acceptor properties and to their ability to form metal complexes and coordination polymers with high thermal stability and display interesting luminescence, nonlinear optical, electrochemical, and H 2 storage properties.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent water binding we decided to include tetrazolate groups in higher denticity ligands. [16] Bipyridine and terpyridine were chosen as suitable building blocks because their chemistry is well known and the coordination properties of bipyridine-carboxylate and terpyridine-carboxylate ligands and the luminescent properties of their lanthanide complexes have been extensively investigated. [10,[23][24][25] This should allow for a facile comparison of the effect of tetrazolate substitution with respect to carboxylate on the excitation wavelength and luminescence quantum yields of isostructural lanthanide complexes.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the most used methods toward the synthesis of the 1,5-DS-1H-T are both click [3 + 2] dipolar cycloadditions of organic azides with cyanides [4][5][6][7] and the Ugi-azide reaction between amines, aldehydes, isocyanides and hydrazoic acid [8]. , allowing the synthesis of various potent luminescent materials [9]. The bis-sulfide-tetrazoles 4, which were biologically tested by Waisser and co-workers, showed a strong antiulcer, as well as antimycobacterial activity [10].…”
Section: Introductionmentioning
confidence: 99%